2020
DOI: 10.1007/s13201-019-1122-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of conceptual and physical rainfall–runoff models

Abstract: The design of water resource structures needs long-term runoff data which is always a problem in developing countries due to the involvement of huge cost of operation and maintenance of gauge discharge sites. Hydrological modelling provides a solution to this problem by developing relationship between different hydrological processes. In the past, several models have been propagated to model runoff using simple empirical relationships between rainfall and runoff to complex physical model using spatially distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(47 citation statements)
references
References 52 publications
0
46
0
1
Order By: Relevance
“…In some cases, the lumped conceptual models have been found to perform better than physically based models. For instance in the study by Jaiswal et al [98], for calibration, AWBM and TANK yield NSE values of 0.76 and 0.84, respectively, while SWAT had NSE of 0.75. However, in other areas, some rainfall-runoff models can exhibit unsatisfactory performances.…”
Section: Model Performance For the Calibration Validation And Entirementioning
confidence: 99%
“…In some cases, the lumped conceptual models have been found to perform better than physically based models. For instance in the study by Jaiswal et al [98], for calibration, AWBM and TANK yield NSE values of 0.76 and 0.84, respectively, while SWAT had NSE of 0.75. However, in other areas, some rainfall-runoff models can exhibit unsatisfactory performances.…”
Section: Model Performance For the Calibration Validation And Entirementioning
confidence: 99%
“…Examples of these include the TANK model [ 264 ], Hydrologic Engineering Center's Hydraulic Modeling System (HEC-HMS) [ 265 , 266 ], TOPMODEL, Système Hydrologique Européen (SHE), Soil and Water Assessment Tool (SWAT) [ 267 , 268 ] and complex conceptual models such as MODified HYDROLOG (MODHYDROLOG) [ 269 ]. A review of the pros and cons of these models by Sivapalan et al [ 270 ] and Jaiswal et al [ 271 ] revealed that distributed physically based models have the advantage of accounting for spatial heterogeneities and provide detailed description of the hydrological processes in a catchment with limited demands of input data hence their widespread use in numerous hydrological studies [ 266 , 272 – 276 ]. The same notion was confirmed by the World Meteorological Organization [ 181 ] in their inter-comparison of conceptual hydrological models for operational hydrological forecasting.…”
Section: Hydrological Modellingmentioning
confidence: 99%
“…One of the main effects of urban green infrastructure on runoff water quality is the overall reduction in runoff quantity, thereby reducing the quantity of pollutants reaching urban waterways and the sewer infrastructure (Gooré Bi et al, 2015). Research on urban rainfall and runoff pollution mainly includes the following aspects: the spatial and temporal distribution of urban stormwater runoff pollutants (Brezonik and Stadlemann, 2002;Jeffrey et al, 2005;Geonha et al, 2007); the pollution characteristics of stormwater runoff produced by different underlying surfaces such as urban asphalt pavement (Ellis, 2000) and green pavement (Huang et al, 2006); the controlling effect of urban greening on pollutants (Ren et al, 2005;Chen et al, 2009;Ren et al, 2020;Xu et al, 2020); and the erosive effect of stormwater runoff and the development on urban rainfall-runoff models (Murakami et al, 2008;Ouyang et al, 2010;;Jaiswal et al, 2020). Among them, studying the characteristics of urban rainfall and runoff products is the basis for in-depth research on urban areal source pollution.…”
Section: Introductionmentioning
confidence: 99%